Market systems change rubric - Loveridge, Donna (Oxford Policy Management, 2022)
This systems change rubric describes different performance levels acco rding to various systems elements, such as policy (formal rules), prac tices and relationships and connections. Programmes can use the rubric to assess the performance of systems to help decide where and how to intervene, or during and post-implementation to conduct progress asses sments, and assess the effectiveness of interventions and type, breadt h and depth of systems change. Each performance level description high lights the type of data and information that needs to be collected. On e analysis is completed, users can compare this to the performance des criptions to see which level best matches the analysis. This helps pro grammes draw conclusions about systems changes. The rubric was develop ed in 2020 and tested in 2021 and builds on systems change thinking an d frameworks from two previous FSG publications. It can be used as: pr e-intervention to conduct an assessment during an intervention to cond uct progress assessments and reflect on the effectiveness of intervent ions to change systems and inform decision making post intervention to make judgements about whether interventions were valuable given the r esources, time and effort spent Useful for: Implementation managers to determine the effectiveness of interventions, as well as by Monitorin g, Evaluation and Learning (MEL) teams to track progress against expec ted outcomes.